The Effect of Operating Procedure with Infection Incidence on Contaminated Cleaning Operating Patients (Case Control Study in RSU HAJI Surabaya) - Eva Agustina; Fariani Syahrul (Universitas Airlangga, 2017)
The hospital is one of the health facilities that provide promotive, preventive, curative and rehabilitative services. The 2014 World Health Organization survey showed the incidence of Surgical Site Infection (SSI) increased by 1.2 cases per 100 surgical procedures to 23.6 cases per 100 surgical procedures. This study aims to analyze the effect of operating procedures on the risk of SSI in clean-contaminated surgery patients. This study uses a case-control research design. This research was conducted at Haji Public Hospital, Surabaya in January 2016 - March 2017. The sample size of the case group was 20 patients and the control group was 20 patients. Sampling is done through a simple random sampling technique. Data collection was performed using secondary data, namely the patient's medical record. The relationship between variables was calculated through the chi-square test using a computer application. The results of statistical analysis showed that the factors that influence the incidence of SSI in clean-contaminated surgery patients at Haji Public Hospital include preoperative bathing (OR = 7.42) and preoperative shaving (OR = 6.00). Factors that did not affect the occurrence of SSI included age (OR = 1.00), nature of surgery (OR = 1.00), body temperature (OR = 1.28), nutritional status (OR = 2.78), and American Society of Anesthesiologists (ASA) score (OR = 2.26). The conclusion of the study is the risk factors that influence the incidence of SSI in clean operating contaminated patients in Haji Public Hospital including preoperative bathing and preoperative shaving. Research suggestions, conducting socialization and supervision of the implementation of standard operating procedures and the use of the SSI prevention bundle as an effort to minimize the incidence of SSI.